Bulgaria : Forest Policy Note - World Bank (Washington, DC, 2014)
This focus note presents key findings of a 2008 report on implementing Financial Action task Force (FATF) standards in developing countries The Financial Sector Reform and Strengthening(FIRST) Initiative funded a five-country study to analyze the effects of anti-money laundering (AML) and combating the financing of terrorism (CFT) regulation on access to finance, especially in low-income populations. Standard AML and CFT measures promote financial integrity and support crime fighting, but they can also exclude low-income people from financial services through onerous regulations. The study identifies factors that may intensify this impact, provides approaches on the design of appropriate AML/CFT controls that complement financial access policies, and suggests key design principles for AML/CFT controls.